Goal Directed Design Method Application on UI/UX of Dua Mata Mobile Apps - Sukarsa, I Made; Piarsa, I Nyoman; Linggar Sukarta, Erlangga Bayu; Wisswani, Ni Wayan (Universitas Negeri Semarang, 2021)
Purpose: Dua Mata is a mobile and website-based community service application intended for residents of South Kuta. Evaluation of existing designs is needed to assess whether the user interface design can provide user satisfaction. The aim this paper to evaluate the UI/UX of Dua Mata using QUIM method. Methods: Research, Modeling, requirement definition, Framework Definition, and Refinements are the step of the GDD method. The QUIM method aims to prioritize indicators that need to be fixed in the old design: Resource Utilization, Minimal Memory Load, and Security. Modeling determined respondents who will do the second test and in requirement definition stage scenarios are chosen. The selected scenario is registering, forgetting passwords, searching directories, ordering, and adding services. The framework definition and refinement is the stage of making a wireframe then prototype and tested. Result: The test results showed a big decrease in the scenario completion time by 39.41 seconds in the register scenario. The score on the Resource Utilization indicator has increased by 8 points, the Minimum Memory Load indicator is 9 points and the Security indicator is 6 points. Novelty: The novelty is that the increasing of the Resource Utilization indicator indicates the new design has a higher level of user satisfaction than the old design